Elastic Dynamics Modeling and Characteristic Analysis of a 3T Isotropy Parallel Mechanism - Hong Zhang; Panpan Li; Tongde Wang (Jixie chuandong)
In order to improve the motion accuracy of the parallel mechanism， the influence of the flexible deformation produced by the branched chain on the motion trajectory of the 3T isotropic parallel mechanism during the movement is studied and summarized. Firstly， according to the structure of the parallel mechanism， its kinematics characteristics are analyzed. Secondly， by using the elastic dynamics model of the space beam element， the Lagrange equation， the finite element theory and the kinematics and dynamics constraints of each branch chain， the elastic dynamics equations of the three branches are established under the flexible deformation condition， and the solution is solved based on the Newmark method. Finally， the ANSYS and ADAMS software are used to carry out the elastic dynamics simulation of the parallel mechanism. Through the comparison of the theoretical value and the simulation value of the mechanism model， it is found that the three branched chains have an important influence on the kinematic characteristics of the 3T parallel mechanism under the flexible deformation conditions， and further prove the reliability of the elastic dynamics model of the parallel mechanism， which provides an important theoretical basis for the future research and application.